The EU in the 21st Century
X, 317 p. 8 illus., 4 illus. in color.
Keywords: In the light of Brexit, the migration crisis, and growing scepticism regarding the European integration process, this book offers a comprehensive overview of the most pressing problems facing the European Union in the 21st century. Written by experts from various disciplines, the contributions cover a wide range of economic, legal, social and political challenges, including populism, migration, Brexit, and EU defence, foreign policy and enlargements. Each paper includes a historical account, insights into the problems and challenges confronting the EU, and an assessment of the institutions and policy instruments applied by the EU in response. Discussing each of the problems as part of a process – including the historical roots, current situation and potential solutions – the book allows readers to gain an understanding of the European Union as a living project.